(untitled) (Analele Universității București. Limba și literatură română, 2025)
The present paper identifies various types of dislocation in Dimitrie Cantemir’s Divanul. Dislocation occurs in both noun phrases and verb phrases and can be either simple (involving the inversion of syntactically linked elements) or complex (involving forms of anteposition that entail morphosyntactic or syntactic dislocations). As an erudite scholar, Cantemir’s writing style was influenced by Latin, Greek, and probably Turkish syntax. Given that similar dislocations can also be found in Dosoftei’s work, we may assume that the high frequency of syntactic dislocations indicates that word order was not yet fixed in Old Romanian and that linguistic contact played a role in shaping the language of the period under study.